DalÄlah al-KhafÄ« wa ÄliyÄt al-IjtihÄd: DirÄsah Uá¹£uliyyah bi Iá¸¥Älah KhÄá¹£á¹£ah ilÄ Qaá¸iyah al-Qatl al-Raá¸¥im - Anwar, Syamsul (Al-Jamiah: Journal of Islamic Studies, 2003)
This article deals with an uá¹£Å«lÄ« concept known among the Hanafi legal theoretician under the name of dalÄlÄt al-khÄf (the denotation of an obscure text) and its relation to the mechanism of ijtihÄd with special reference to the case of euthanasia. The author examines the meaning of the obscure text (al-khÄfiy) and discusses the mechanism followed by the uá¹£Å«lÄ« in clarifying the ambiguity in it, taking euthanasia as an example. From this, the author concludes that the process of legal reasoning in founding out a legal rule for a case involves three poles which have dialectical relations to one another: the text, the reality, and the objective of law. The text with its symbolic characteristic and its relying upon generalization and abstraction in expressing an object enables the mujtahid to add a new meaning to it and this meaning is produced through an adequate understanding of the case and the spatio-temporal space in which it happens in the one hand and through considering the objective of law as meaning space on the other hand. The reality of the case shades Â light in our understanding of the text, while the text in the same time gives us a clear orientation in coping with the reality.